S.C.C.O.R.E Model dan Budaya Etis Organisasi Terhadap Penyalahgunaan Aset - Marissa Sinaga; Abdul Rohman (Politeknik Ganesha Medan, 2025)
This study evaluated how pressure, opportunity, rationalization, capability, ego, collusion, and organizational ethical culture influence asset misuse. The research included 294 employees from non-ministerial government agencies in Indonesia, selected using a simple random sampling technique. Data were collected through a questionnaire distributed via Google Forms. To analyze the data, this study used the Structural Equation Modeling Partial Least Square (SEM-PLS) approach. This study found that the variables of capability and ego have no significant influence on asset misappropriation; the variables of pressure, opportunity, rationalization, collusion, on the other hand, have a positive and significant influence on asset misappropriation. Organizational ethical culture can reduce the influence of pressure on asset misappropriation but cannot reduce the influence of opportunity, rationalization, capability, ego, collusion on asset misappropriation. This research helps the government make policies to reduce fraud, especially asset misappropriation. Furthermore, the findings of this study can serve as an evaluation guide to enhance fraud prevention efforts in the workplace, particularly for Indonesian government institutions outside the ministries included in this study